Tracing interpersonal discursive features in Australian nursing bedside handovers: Approachability features, patient engagement and insights for ESP training and working with internationally trained nurses. (April 2022) - Dahm, Maria R.; Slade, Diana; Brady, Bernadette; Goncharov, Liza; Chien, Laura
Abstract: Bedside handovers in clinical nursing are crucial communicative events fostering involvement of patients in their care. Communication challenges between nurses and patients threaten quality of care and hinder patient involvement. Knowledge and in-depth understanding of how these specialised interactions are co-constructed discursively is limited, but necessary to inform English for specific purposes training and to improve patient participation. We trace the interpersonal discursive features of communication between nurses and patients across four case studies of bedside handovers recorded at two metropolitan Australian hospitals. Handovers were selected for contextual factors: patients' language background (native or non-native English speaking (NES/NNES)) and presence of family/carers. By applying a deductive framework of discursive approachability features, combined with an inductive analysis of discourse features in context, we describe which communication behaviours facilitate or hinder patient participation. We discovered that incoming and outgoing nurses used different discursive strategies during handover. Outgoing nurses made fewer efforts at being approachable to patients and family/carers, impeding patient involvement. Incoming nurses were more approachable, inviting patient participation and building interpersonal connections. NES patients and carers were more involved in handover despite outgoing nurses' disengaging communication behaviours. Findings can inform reflective practice and communication skills training among practicing and trainee nurses. Highlights: A new framework of discursive approachability features guided handover analysis. Outgoing nurses displayed more negatively geared approachability features. Outgoing nurses discursively impede patient participation in bedside handovers. Incoming nurses displayed more positively geared approachability features. Incoming nurses discursively invite patient participation and foster relationships.